2011
DOI: 10.1038/emboj.2011.360
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear retention of importin α coordinates cell fate through changes in gene expression

Abstract: Various cellular stresses including oxidative stress induce a collapse of the Ran gradient, which causes accumulation of importin a in the nucleus and a subsequent block of nuclear protein import. However, it is unknown whether accumulated importin a performs roles in the nucleus after its migration in response to stress. In this study, we found that nuclear-retained importin a2 binds with DNase I-sensitive nuclear component(s) and exhibits selective upregulation of mRNA encoding Serine/threonine kinase 35 (ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
96
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 56 publications
11
96
0
Order By: Relevance
“…4), which may possibly lead to decreased proliferation. A previous study showed that ectopic expression of STK35 could enhance caspase-independent cell death under oxidative stress [11]. Here, STK35 knockdown significantly increased the activity of caspase 3 and caspase 7, two major executioner caspases [19] (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4), which may possibly lead to decreased proliferation. A previous study showed that ectopic expression of STK35 could enhance caspase-independent cell death under oxidative stress [11]. Here, STK35 knockdown significantly increased the activity of caspase 3 and caspase 7, two major executioner caspases [19] (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Importin α2 can bind to the promoter region of STK35 and induce its transcription [11]. The present report tried to investigate the upstream mediator of STK35 expression in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, roles have been described for Kpna2 and Kpna4 in somatic and germ cell responses to oxidative stress respectively, which appears to be through a direct influence on gene expression (Yasuda et al 2012, Young et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that PAP2 and MDH might be negatively regulated in the SI response. The interaction network showed that PAP2 was negatively induced by CPN10 through the link of importin alpha isoform 6 (At1g02690), which could rapidly accumulate in the nucleus in response to stress (Yasuda et al, 2012). MDH was negatively induced by glutathione transferase and PYR6 through links of RNA polymerase I subunit 43 (At1g60620) and 6-phosphogluconate dehydrogenase family protein (At1g64190), respectively.…”
Section: Discussionmentioning
confidence: 99%